The Physiological and Mental Efects of the Fran Benchmark Crossfit Workout at Diferent Competitive Stages; [Wpływ Treningu Crossfit Na Parametry Poznawcze I Fizjologiczne W Zależności Od Poziomu Rywalizacji] - Aedo-Munoz, E (Polish Academy of Sciences, Institute of Slavic Studies, 2024)
This study investigates the acute effects of CrossFit training on cognition and physiological parameters across different performance stages. We focused on evaluating the impact of such training on both the mental and physical performance of athletes classified as Elite, Advanced, and Beginners. The objective was to explore how CrossFit, known for its high-intensity and varied functional movements, influences cognitive functions and physiological responses in athletes of varying expertise. By comparing these groups both before and after the Workout of the Day (WOD), we aimed to understand the relationship between CrossFit training intensity and cognitive and physiological changes. Methodologically, our approach involved categorizing our sample into three groups: Elite (n=7), Advanced (n=10), and Beginners (n=15). We conducted comprehensive assessments of each participant’s cognitive and physiological parameters pre-and post-WOD. The results revealed notable differences in performance time, with Elite athletes showing significantly quicker times compared to Advanced and Beginners. Cognitive functions, particularly executive functions like reading, counting, choice-making, shifting, inhibition, and flexibility, also varied significantly across the groups. Physiological measurements, including lactate stages and heart rate, further highlighted these differences. Remarkably, Elite athletes exhibited a 13.1 mmol average lactate level, lower than their counterparts, and a higher average heart rate of 188.0 bpm. In terms of cognitive functions, differences were observed in various executive tasks, showcasing the nuanced impact of high-intensity exercise on cognitive abilities. In conclusion, our study provides compelling evidence that high-intensity CrossFit training positively influences executive functions. These findings are quantified through substantial variations in performance times, executive function tasks, lactate stages, and heart rates, offering critical insights into the multi-dimensional benefits of CrossFit training across different competitive stages. © The Authors 2024.